Diseño y desarrollo de una herramienta SIG para estimar las compensaciones bióticas en el contexto colombiano (2023)
The selection of the mandatory input variables was carried out and a Model Builder type toolbox was developed in ArcGis Pro. Six models were designed and developed, for which six user stories were also defined, establishing field of application, scope and usefulness of each model that makes up the tool.